Usage of methods, which develop skills of entrepreneurship, during financial field lectures at Siauliai State College - Kušleikienė, Lina; Šivickienė, Renata (Buhalterinės apskaitos teorija ir praktika, 2014)
Entrepreneurship – can be defined as a person’s ability to implement their ideas, which manifests itself through this innovation, creativity, self-confidence, openness to innovation, the ability to plan, lead, take risks. Entrepreneurship education goal – to develop students’ skills necessary for them as individuals and as members of society to live independently and positively affect their families and society, enabling them to take responsibility and the ability to live in a society based on a market economy. It is necessary to develop these entrepreneurial skills competencies: 1) the ability to solve problems; 2) the ability to build relationships; 3) self-confidence; 4) personal initiative showing. Entrepreneurial skills are needed on a daily basis in all areas of life: seeking employment, working, building a business and making important decisions in everyday life. It is important that colleges have developed entrepreneurial environment, encouraging student initiative, implemented design training, strengthening the link between theory and practice, a more flexible organization of teaching and learning. The aim – to reveal the importance of methods, used for developing entrepreneurship skills in financial field lectures. The study was conducted in Siauliai state college. In the study were prepared a questionnaire for students. The study were interviewed a total of 100 students. Upon analysis of the data suggests that in order to develop entrepreneurial competence, students are motivated and willing to try out new techniques. All the students understand what they lack knowledge and skills as well as what problems they could encounter. Active methods cover preparations of business plans, visits at business company, projects, computer modelling, imitation of role.